2020
DOI: 10.1039/c9tb02728a
|View full text |Cite
|
Sign up to set email alerts
|

A sustained zero-order release carrier for long-acting, peakless basal insulin therapy

Abstract: A new drug carrier, which mimics physiologic basal insulin, and secretes and releases insulin at a constant rate, was designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Hollow capsules fabricated via LbL assembly of polymers comprise an ultrathin permeable shell (<50 nm) that participates in various types of interactions (Mathivanan et al, 2019 ; Wang et al, 2020 ) and microsized or nanosized cavities that deposit drugs or active molecules. The shells are able to trigger the release of loaded molecules to protect the load from external stress and thus extend the time of release.…”
Section: Medical Applications Of Ta Self-assemblymentioning
confidence: 99%
See 3 more Smart Citations
“…Hollow capsules fabricated via LbL assembly of polymers comprise an ultrathin permeable shell (<50 nm) that participates in various types of interactions (Mathivanan et al, 2019 ; Wang et al, 2020 ) and microsized or nanosized cavities that deposit drugs or active molecules. The shells are able to trigger the release of loaded molecules to protect the load from external stress and thus extend the time of release.…”
Section: Medical Applications Of Ta Self-assemblymentioning
confidence: 99%
“…To achieve a persistent, flat, and stable insulin supply, a new drug carrier was designed. Wang et al ( 2020 ) assembled PEG–insulin and TA into a film, which can release PEG–insulin into the medium through a reversible, dynamic hydrogen bond. In addition, the unique release mechanism of the films explained the unique release kinetics of PEG–insulin, which had zero-order kinetics.…”
Section: Medical Applications Of Ta Self-assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] When these films are fabricated from monodisperse polymers, zero-order release can be achieved. [24][25][26][27][28][29] Using this principle, dynamic LBL films of PEGylated leuprolide (PEG-LEU) and tannic acid (TA) were fabricated using dynamic hydrogen bonding as the driving force. Both in vitro and in vivo tests revealed that drug release from the film followed perfect zero-order kinetics.…”
Section: Introductionmentioning
confidence: 99%